Understanding Indonesian Students Mathematics Performance: A Secondary Analysis of PISA Data - Mardhiah MZ; Mailizar Mailizar; Elizar Elizar (Universitas Syiah Kuala, 2025)
This study aims to identify factors affecting Indonesian students achievement in mathematics based on the last three period of PISA data; 2012, 2015, and 2018..Structural Equation Modelling (SEM) was employed in this study. The population of this study were 15 years old Indonesian students.On the other hand, the sample is composed5.622 students, 6513 students, and 12.098 studentsfor those each three periods.The data were obtained from OECD website. The result shown there is a high and positive relationship between mathematics achievement with mathematics self-concept and socioeconomic status. The medium and positive effect can be seen in motivation variable. It has also been determined that the variable mathematics anxiety has a negative and small effect on mathematics achievement. According to the results of the research study there is no meaningful relationship between variables of sense of belonging, self-efficacy, and mathematics achievement of Indonesian students.